Changes of Passenger Preferences in Air Transportation - Baráth, M. (Acta Technica Jaurinensis, 2013)
Airlines and airport companies often conduct surveys of their passengers to get to know their present and latent needs. The purpose of this article is to reveal the differences between the preferences of business and leisure passengers in general and their recent changes in particular. The basis of this paper is a survey about passengers’ travel preferences not taking into account carriers. In the article the preparation of the survey and the results of it are going to be discussed.